1991
DOI: 10.1055/s-2007-1019984
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Results of the Modified Waterston Shunt with PTFE Grafts for Palliation of Complex Congenital Cyanotic Heart Disease in Neonates

Abstract: During a 12 year period from 1978 to 1989, 35 infants under 4 weeks of age underwent palliative surgery for complex congenital cyanotic heart disease with a short (1-1.5 cm) PTFE graft between the ascending aorta and the right pulmonary artery (modified Waterston shunt). Twenty-three infants had pulmonary atresia and 14 had severe pulmonary stenosis. Underlying cardiac lesions were tetralogy of Fallot (n = 11), single ventricle (n = 7), transposition complexes (n = 6), and intact ventricular septum and hypopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…1,[16][17][18] With the modified PTFE shunt grafts, early shunt failure is in the range of 0-30%. 1 Woolf et al found that the incidences for early shunt failure, mortality at revision of early shunt failure and overall hospital mortality proved all to be lower for the PTFE shunt in comparison not only to the original Waterston shunt but also to the Blalock-Taussig shunt. 19 Fontan and Baudet showed that 'right heart bypass' is a clinically successful approach to the management of tricuspid atresia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,[16][17][18] With the modified PTFE shunt grafts, early shunt failure is in the range of 0-30%. 1 Woolf et al found that the incidences for early shunt failure, mortality at revision of early shunt failure and overall hospital mortality proved all to be lower for the PTFE shunt in comparison not only to the original Waterston shunt but also to the Blalock-Taussig shunt. 19 Fontan and Baudet showed that 'right heart bypass' is a clinically successful approach to the management of tricuspid atresia.…”
Section: Discussionmentioning
confidence: 99%
“…Waterston and Potts anastomoses have been widely replaced by other procedures. 1 So far, cardiac catherization has been defined as the gold standard in preoperative imaging of congenital heart defects.…”
Section: And Cooley Andmentioning
confidence: 99%
See 3 more Smart Citations